WORK CONDITION FACTORS AND EMPLOYEE ENGAGEMENT: THE MEDIATING ROLE OF PSYCHOLOGICAL CAPITAL - Ononye Uzoma Heman; Olayemi Olufemi Olabode; Abiegbe Amram (Management Study Program, Faculty of Business and Economics, Petra Christian University, 2024)
Work conditions influenced employee engagement, but its influence was still unclear owing to its multifaceted nature and variations across professions and industries in highly dynamic environments. In addition, studies on the psychological mechanisms explaining this relationship were limited. The study examined specific work condition factors comprising leader-member exchange and role clarity as influences on employee engagement, given psychological capital as a mediating variable. Data were obtained from 231 customer-contact employees working in hotels in two major cities, Asaba and Warri, in Delta State, Nigeria, and analyzed using the partial least squares analytical procedure. The study found that leader-member exchange and role clarity relationships with employee engagement were positive and significant, and psychological capital mediated these relationships. Also, role clarity and psychological capital sequentially mediated the relationship between leader-member exchange and employee engagement. The study contributed an integrated research framework that uncovered the sequential effect of leader-member exchange on employee engagement and the simple and sequential mediation of psychological capital in this framework. The practical implications of the findings were discussed for improving employee engagement.